Coinfection With Trypanosoma brucei Confers Protection Against Cutaneous Leishmaniasis - Pereira, Lais; Oliveira, Fabiano; Townsend, Shannon; Metangmo, Sonia; Meneses, Claudio; Moore, Ian N.; Brodskyn, Claudia I.; Valenzuela, Jesus G.; Magez, Stefan; Kamhawi, Shaden (Frontiers in Immunology, 2018)
Abstract Infection with certain bacteria, parasites and viruses alters the host immune system to Leishmania major influencing disease outcome. Here, we determined the outcome of a chronic infection with Trypanosoma brucei brucei on cutaneous leishmaniasis (CL) caused by L. major. C57BL/6 mice infected with T. b. brucei were given a sub-curative treatment with diminazene aceturate then coinfected with L. major¬ by vector bites. Our results revealed that infection with T. b. brucei controls CL pathology. Compared to controls, coinfected mice showed a significant decrease in lesion size (P<0.05) up to 6 weeks post-infection and a significant decrease in parasite burden (P<0.0001) at 3 weeks post-infection. Protection against L. major resulted from a non-specific activation of T cells by trypanosomes. This induced a strong immune response characterized by IFN-γ production at the site of bites and systemically, creating a hostile inflammatory environment for L. major parasites and conferring protection from CL.